2022
DOI: 10.1111/jonm.13729
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of patient safety culture among emergency room nurses in Jordanian accredited hospitals

Abstract: Aim The aim of this study is to assess the perceptions of patient safety culture among emergency room nurses in Jordan. Background Patient safety culture is considered an international priority for health care institutions. There is a lack of studies on patient safety culture among emergency room nurses in international and Arab countries including Jordan. Methods A cross‐sectional design was used to perform among emergency room nurses (N = 424) who are working in two health sectors (government and private) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(60 reference statements)
3
5
0
Order By: Relevance
“…The participants with postgraduate degrees and having 11 years of experience or more showed higher awareness than other groups, the results agreed with study conducted among Jordanian nurses [50]. Studies described that when experience and education increases, hospital quality of service also increase [14,26].…”
Section: Discussionsupporting
confidence: 85%
“…The participants with postgraduate degrees and having 11 years of experience or more showed higher awareness than other groups, the results agreed with study conducted among Jordanian nurses [50]. Studies described that when experience and education increases, hospital quality of service also increase [14,26].…”
Section: Discussionsupporting
confidence: 85%
“…et al (2018), Asadi et al (2019), Al-Shyyab et al (2023), Najar et al Aouicha et al (2021), and Buchenek et al (2023), teamwork in organizational units obtained the highest score(23, 28,(30)(31)(32).Their results are consistent with the results of the present study.The results also revealed a statistically signi cant relationship between safety culture, level of education, and employment history of emergency department nurses. In the study byMalak et al (2022) revealed a statistically signi cant relationship between the patient safety culture and the level of education of emergency nurses in Jordanian hospitals(33). Alquwez et al (2018) also obtained similar results in their study(34), which is consistent with the results of the present study.…”
supporting
confidence: 89%
“…By using this approach, healthcare facilities are better able to anticipate problems, grab opportunities, and maximise efficiency. Strategic management could significantly improve healthcare quality and effectiveness in the Jordanian healthcare system (Malak et al, 2022). This is because hospitals in Jordan operate under the limitations of limited resources and complicated regulatory frameworks.…”
Section: Background and Significancementioning
confidence: 99%
“…The majority of the healthcare in the country is provided by public institutions. These hospitals usually experience shortages of both financial resources and human labour, as well as outdated infrastructure and equipment (Malak et al, 2022). The healthcare system is struggling under the weight of an ageing population and a rise in the incidence of chronic illnesses.…”
Section: Current Healthcare Landscape In Jordanmentioning
confidence: 99%